2014
DOI: 10.1007/s12155-014-9433-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Corn Residue Harvest Management on Grain, Stover, and Energy Yields

Abstract: Economic, environmental, and energy independence issues are contributing to rising fossil fuel prices, petroleum supply concerns, and a growing interest in biomass feedstocks as renewable energy sources. Potential feedstocks include perennial grasses, timber, and annual grain crops with our focus being on corn (Zea mays L.) stover. A plot-scale study evaluating stover removal was initiated in 2008 on a South Carolina Coastal Plain Coxville/Rains-GoldsboroLynchburg soil association site. In addition to grain an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Mourtzinis et al [69] showed that harvesting the above-ear corn plant fraction, while leaving the remaining stover in the field for soil erosion protection and soil organic matter maintenance, is a potential option for corn stover harvest in the Southeast. Other research concluded that harvesting the upper half of standing stover with cobs produced the highest quality feedstock and maintained soil productivity as determined by the soil management assessment framework (SMAF) [70,71]. Total precipitation and average air temperature during the growing season were strongly correlated with stover chemical composition, and the above ear portion of stover was more desirable due to lower lignin and higher cellulose content [72].…”
Section: Corn Stover Removalmentioning
confidence: 99%
“…Mourtzinis et al [69] showed that harvesting the above-ear corn plant fraction, while leaving the remaining stover in the field for soil erosion protection and soil organic matter maintenance, is a potential option for corn stover harvest in the Southeast. Other research concluded that harvesting the upper half of standing stover with cobs produced the highest quality feedstock and maintained soil productivity as determined by the soil management assessment framework (SMAF) [70,71]. Total precipitation and average air temperature during the growing season were strongly correlated with stover chemical composition, and the above ear portion of stover was more desirable due to lower lignin and higher cellulose content [72].…”
Section: Corn Stover Removalmentioning
confidence: 99%
“…C orn crop residue harvest by chopping silage, baling stover,or grazing occurs on about 40% of Nebraska's 3,700,000 ha of corn land, primarily for feeding of beef (Klopfenstein et al, 2013) and may increase to meet future feedstock demands for ethanol production (Cantrell et al, 2014; Alternative Fuels Data Center, 2014; DuPont Cellulosic Ethanol. 2012; Biomass Research and Development Board, 2009).…”
mentioning
confidence: 99%
“…Precipitation and temperature patterns were highly correlated with stover composition indicating that in addition to their effect on biomass yield, weather patterns may have multiple effects on potential biofuel production. Cantrell et al [16] provides a final insight regarding the use of corn stover for bioenergy by quantifying gross energy distribution within various plant fractions. Based on 4 years of research, they conclude that harvesting 25 to 100 % of the above-ground biomass could supply between 30 and 168 GJ ha −1 depending upon annual rainfall.…”
mentioning
confidence: 99%